2019
DOI: 10.1002/jsde.12299
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in the Safety of Use of Hand Dishwashing Liquids through the Addition of Sulfonic Derivatives of Alkyl Polyglucosides

Abstract: The effect of a sulfonic acid derivative of alkyl polyglucosides on the safety of hand dishwashing liquids was assessed. In this study, it was found that an increase in the concentration of the natural origin raw material in samples led to a decrease in the zein number, and reduced changes in the pH level of bovine serum albumin solution, compared to a reference sample formulated without these compounds. These findings suggest a high level of reduction in the skin‐irritation effect after applying hand dishwash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
(103 reference statements)
0
8
0
Order By: Relevance
“…The skin pretreatment by degreasing represented a potential risk of removing dermal lipids and bacterial flora, to which Seweryn el al. [28] draw attention. From the pH values after the topical application of matrices containing honey and bee products, it can be concluded that no disruption of natural acid skin mantle was detected, which enables an indirect prediction of the influence of studied matrices on the skin.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The skin pretreatment by degreasing represented a potential risk of removing dermal lipids and bacterial flora, to which Seweryn el al. [28] draw attention. From the pH values after the topical application of matrices containing honey and bee products, it can be concluded that no disruption of natural acid skin mantle was detected, which enables an indirect prediction of the influence of studied matrices on the skin.…”
Section: Sensory Analysismentioning
confidence: 99%
“…The zein value measurement is a suitable research method enabling determination of the skin irritation potential of surfactants and surfactant-based finished cosmetics and household chemicals according to many reports [ 11 , 12 , 13 , 14 , 15 , 17 , 18 , 42 , 43 , 94 , 95 ]. The method is based on the structural resemblance of the zein protein and the keratin protein building the epidermis.…”
Section: Resultsmentioning
confidence: 99%
“…Developmental trends in household chemistry indicate a growing interest in formulations based on natural raw materials [ 5 , 6 , 7 ]. This can be explained in terms of the growing environmental awareness of consumers [ 8 , 9 , 10 , 11 ] and various aspects of safety of use [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. As the result, the market is offering an increasing number of products which are entirely based on natural raw materials or have some content of natural additives, such as fragrance compositions [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is worth noting that alkylphenols and other APE derivatives are a class of endocrine disrupters, and they would be even suspected of interfering with the hormonal system of wildlife. 18 On the contrary, some sugar-based surfactants such as alkyl polyglycosides (APGs), 8 glucamide, 17 and sugar ester 19 are also categorized as nonionic surfactants. Furthermore, traditional APGs and alkyl glycosides (AGs) have less damage to the human body or the negative effect on the fragile ecological environment in the actual use.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the hydrophilic head groups of the sugar-based surfactants consist of monosaccharides, disaccharides, other oligosaccharides, and even carbohydrate derivatives, which retain the advantages of the nonionic surfactants. , So far, they showed a number of excellent properties such as low/no toxicity, nonirritation, solubility, surface activity, biocompatibility, and biodegradability besides utilizing the abundant renewable resources and reducing the high rate of the global petroleum consumption. With the advantage of renewable/rich/cheap plant-derived carbohydrates, sugar-based surfactants including the well-known glycolipid are inevitably engaged in the dedicated conventional application fields such as hand dishwashing liquids, oil recovery, industrial cleaners, agriculture, food, and soil remediation. Furthermore, with the in-depth study of glycolipid surfactants, they are used in special areas such as membrane protein extraction and pharmaceuticals and for wetting, dispersing, and emulsifying properties.…”
Section: Introductionmentioning
confidence: 99%